The growing concern of MDR/XDR bacteria in patients undergoing dialysis: a cross-sectional study - Noor S. Kadhem; Ahmed Khassaf Atya (Počki)
Background. Dialysis patients are at heightened risk for multidrug-resistant (MDR) and extensively drug-resistant (XDR) bacterial infections due to their vulnerability to infections and frequent exposure to healthcare environments. This study aims to determine the prevalence, risk factors, and antimicrobial resistance patterns of these pathogens to enhance patient care and infection control strategies. Materials and methods. This cross-sectional study was conducted at the Al-Hussein Teaching Hospital Dialysis Unit in Thi-Qar, Nasiriyah, Iraq, from September to December 2024, involving 121 dialysis patients. Data collected from participants included demographic information, comorbidities, and dialysis-related parameters. Microbiological analysis involved urine sample processing through bacterial culture, with bacterial identification and antimicrobial susceptibility testing performed using the VITEK 2 Compact system. Results. The mean age of the study population was 55.0 ± 16.6 years, with a higher proportion of males (52.9 %). Diabetes mellitus was the most common comorbidity, affecting 70 % of patients either alone or in combination with hypertension and cardiovascular disease. The culture positivity rate was 19.0 %, with E.coli being the most frequently isolated pathogen (65.2 %), followed by K.pneumoniae (21.7 %) and E.cloacae (13.1 %). Antimicrobial resistance testing revealed that 60 % of E.coli and all K.pneumoniae isolates were MDR, while 40 % of E.coli and 33.3 % of E.cloacae were XDR. A significant negative correlation was observed between dialysis duration and infection frequency (r = –0.2285, p = 0.0117), indicating a higher likelihood of infections during the initial year of dialysis therapy. Conclusions. The findings underscore the high prevalence of MDR/XDR bacterial infections among dialysis patients, particularly during the early stages of treatment. This highlights the urgent need for enhanced infection control measures, robust antimicrobial stewardship programs, and regular surveillance within dialysis facilities. Targeted interventions are essential to reduce infection-related morbidity and mortality among this vulnerable patient population.